Emergent Social Entrepreneur Archetypes in India : An Evolving Viewpoint From a Pilot Analysis - Rao, Nidhish; Praveen, Shilpa; Sankaran, K. (AMC Indian Journal of Entrepreneurship, 2023)
Though many social entrepreneurs carry similar motivations to solve critical social issues, they differ in the types of problems to be addressed and their overall approach or orientation towards social issues. Surprisingly, barring few studies research studies have largely remained silent on these differences among social entrepreneurs. Therefore, in the past, experts have emphasized that such classification of social entrepreneurs (archetypes) on a few important criteria at any given point in time would greatly inform the social entrepreneurship domain. This study addresses this critical gap